Review Article - The 2025 Punjab Landslide: A Comprehensive Review of Causes, Impacts, Mitigation, and Policy Implications - Kumari, Mamta (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The 2025 Punjab landslide was a significant geomorphological event that highlighted the complex interplay between natural processes and human activities in landslide-prone regions. This review synthesizes current understanding of the event’s causes, immediate and longer-term impacts, the effectiveness of mitigation and response measures, and the policy lessons that have since emerged. Emphasis is placed on multidisciplinary analysis—geotechnical, hydrological, climatological, socio-economic, and governance perspectives—to draw practical lessons for risk reduction, community resilience, and sustainable land-use planning. The article concludes with recommended actions for policymakers, engineers, planners, and communities to reduce the likelihood and consequences of future catastrophic slope failures in India.